Increasing Child Marriage in Indonesia during the Covid-19 Pandemic: What Causes It? - Anju Nofarof Hasudungan (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2022)
The purpose of this study seeks to analyze the factors causing the increase in child marriages registered as students during the COVID-19 pandemic. Not only learning loss as a result of the COVID-19 pandemic, but also the increase in child marriage. The research was conducted with a descriptive qualitative approach. Data was collected through literature study, document analysis, distributing questionnaires, observation, and interviews. During the COVID-19 pandemic, the number of child marriages increased by 300 %. From January to June 2020 there were around 34,000 applications for marriage dispensation and around 97% of applications were granted or allowed to marry. This is a drastic increase compared to the total applications in 2019 of 23,700 applications. This makes Indonesia Rank 7 in the World for Child Marriage Cases. The results show that the increase in child marriage in Indonesia is caused by: 1) Changes in learning patterns; 2) The deteriorating economic condition of the family due to COVID-19, these two things are significant factors; 3) belief in religion, family, and customs; 4) the influence of friends who married early into two small factors. The hope is that the government will not let married children stop getting an education. Rather it provides training or courses both to support the economy and parenting.